Capitalism, advanced and “transitional”, unfolded during the financial crisis - Ivan Ribnikar (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu, 2011)
During the crisis, it became evident that the kind of capitalism that was becoming dominant in the developed world over the last twenty or thirty years, so-called it financial capitalism, was the cause of crisis or at least it cannot completely exculpate itself. The growth in debts, credits, finance in general, changing behaviour of financial institutions and bankers, traders, financiers, their very short-term horizon, their huge bonuses, high bank profits, for capitalism unaccepted morals are some of the things, which have come to the surface. How did the financial crisis start and spread out to the whole world; how were the transitional economies of former Yugoslavia affected; what was the theoretical or ideological foundation for the capitalism we had; what is the morality of capitalism or a market economy – these are the questions touched upon in the first chapters. At the end, and as a conclusion of the paper, there are thoughts and/or ideas about the changes in capitalism to be expected. Financial reforms are crucial for the developed world and they may trigger more profound changes. For transitional economies such reforms are neither essential nor sufficient. The financial crisis has just exposed their problems as more serious and more difficult to overcome than previously thought. Their problems are largely the problems of the real sectors of their economies.